The Politics of Natural Resource Enclosure in South Africa and Ecuador - Melissa Hansen; Mine Islar; Torsten Krause (Conservation & Society, 2015)
The paper examines the ways in which states facilitate ′new enclosures′ of natural resources, and the challenges of this as a strategy of development and environmental sustainability. We argue that enclosures introduce significant changes in property regimes, which redefine conditions for the access and control of land and forest, especially for tribal and indigenous communities. In this context, we analyse two state-initiated projects-the iSimangaliso Wetland Park in South Africa, a UNESCO World Heritage site, and the Socio Bosque incentive conservation programme in Ecuador.